TINJAUAN HUKUM ISLAM DAN PASAL 29 UNDANG-UNDANG DASAR 1945 DALAM IMPLEMENTASI TOLERANSI ANTAR UMAT BERAGAMA DI MA’HAD AL-ZAYTUN - Alimatul Zahro, Nur; Ngainnur Rohmah, Siti; Rahim, Abdur (Causa: Jurnal Hukum dan Kewarganegaraan, 2024)
The motto "Bhinneka Tunggal Ika" (Unity in Diversity) reflects the effort to maintain unity in diversity, but achieving harmony is not easy. Article 29 of the 1945 Constitution guarantees freedom of religion, yet intolerance persists. The principle of tolerance in Islam is rooted in equality, justice, and mutual respect. Syaykh Al-Zaytun promotes tolerance at Ma’had Al-Zaytun, aiming to be a center of education for tolerance and peace. The objectives of this research are to examine the perspective of Islamic law in the implementation of religious tolerance at Ma’had Al-Zaytun and to review Article 29 of the 1945 Constitution in the implementation of religious tolerance at Ma’had Al-Zaytun. The research methodology uses a qualitative approach. Primary data sources were obtained through observation, interviews, documentation, and the book Al-Zaytun Sumber Inspirasi by Robin Simanullang. Secondary data sources include Hukum Islam by Sofyan Hasan, Tafsir Al Mishbah by M. Quraish Shihab, and Article 29 of the 1945 Constitution. The results of this study indicate that Ma’had Al-Zaytun implements the principles of Maqasid Syariah, especially in protecting religion (hifdzuddin), by providing religious education that is open and tolerant towards various Islamic schools of thought and other religions. Ma’had Al-Zaytun also welcomes visits from non-Muslim guests, reflecting a commitment to interfaith cooperation and strengthening religious harmony. According to Article 29 of the 1945 Constitution, Ma’had Al-Zaytun guarantees freedom of religion, equality before the law, and encourages interfaith interactions. Ma’had Al-Zaytun plays a significant role in fostering openness, tolerance, and harmony among religious communities in society. Keywords: Tinjauan, Hukum Islam, Pasal 29 Undang-Undang Dasar 1945, Toleransi, Maqasid Syariah